Intensification of extraction of curcumin from Curcuma amada using ultrasound assisted approach: Effect of different operating parameters - Shirsath, S. R.; Sable, S. S.; Gaikwad, S. G.; Sonawane, S. H.; Saini, D. R.; Gogate, P. R. (Ultrasonic Sonochemistry, 2017)
Curcumin, a dietary phytochemical, has been extracted from rhizomes of Curcuma amada using ultrasound assisted extraction (UAE) and the results compared with the conventional extraction approach to establish the process intensification benefits. The effect of operating parameters such as type of solvent, extraction time, extraction temperature, solid to solvent ratio, particle size and ultrasonic power on the extraction yield have been investigated in details for the approach UAE. The maximum extraction yield as 72% was obtained in 1 h under optimized conditions of 35 degrees C temperature, solid to solvent ratio of 1:25, particle size of 0.09 mm, ultrasonic power of 250 W and ultrasound frequency of 22 kHz with ethanol as the solvent. The obtained yield was significantly higher as compared to the batch extraction where only about 62% yield was achieved in 8 h of treatment. Peleg's model was used to describe the kinetics of UAE and the model showed a good agreement with the experimental results. Overall, ultrasound has been established to be a green process for extraction of curcumin with benefits of reduction in time as compared to batch extraction and the operating temperature as compared to Soxhlet extraction.
Keywords: Acrylamide; Cavitation; Curcumin Extraction; Design; Enhancement; Functionalized Silica; kinetics; Microwave; Nanoparticles; Natural-products; Optimization; Phenolic-compounds; Process Intensification; Solid-liquid Extraction; Ultrasound

Multicomponent solvate crystals of 3,5-dinitrobenzoic acid and acetamide and CSD analysis of solvates - Shaikh, Tabrez Rafique; Shelke, Nikita; Tothadi, Srinu (ACS Omega, 2023)
Twelve multicomponent solvate crystals (cocrystal solvates) of 3,5-dinitrobenzoic acid and acetamide were synthesized via slow evaporation method. All crystalline materials were characterized by single-crystal X-ray diffraction. All cocrystal solvates are isostructural, and crystal packing forms continuous channels where some solvent molecules are connected via weak intermolecular interactions with 3,5dinitrobenzoic acid and acetamide. All multicomponent solvate crystals encompass amide-amide dimer homo synthons and form R22 (8) motifs. Moreover, the phase purity of solvate crystals was analyzed by powder Xray diffraction. Further, most of the cocrystal solvates were analyzed by nuclear magnetic resonance and differential scanning calorimetry. Cambridge structural database analysis categorizes solvate propensity in single-crystal structures. The importance of hydrogen bond donor/ acceptor nature, size, and shape of solvents is also discussed in the context of crystallization and crystal packing.
Keywords: Co-Crystals; Design; Host Guest Complex; solvent

Visible-light-active unsymmetrical squaraine dyes with pyridyl anchoring groups for dye-sensitized solar cells - Deshmukh, Shivdeep Suresh; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Langmuir, 2023)
Visible-light-active alkyl group-wrapped unsymmetrical squaraine dyes SD1-SD3 were synthesized, featuring an indoline donor and pyridine and carboxylic acid anchoring groups. Their photophysical, electrochemical, and photovoltaic characteristics were examined by fabricating a dye-sensitized solar cell (DSSC) device. Both carboxylic acid and pyridine anchoring groups containing squaraine dyes SD3 and SD2 possess similar photophysical and electrochemical characteristics. However, their photovoltaic performances were completely different. The SD3 dye with the carboxylic acid anchoring group displayed a DSSC device efficiency of 7.20% (V-OC 0.81 V; J(SC) 12.29 mA/cm(2)) using iodolyte (I-/I-3(-)) electrolyte, compared to SD1 (V-OC 0.659 V; J(SC) 4.97 mA/cm(2); and eta - 2.34%) and SD2 (V-OC 0.629 V; J(SC) 1.68 mA/cm(2); and eta - 0.84%), which were featured with pyridyl anchoring groups. These results were attributed to dye loading on the Lewis and Br & oslash;nsted acidic sites of TiO2 and the importance of aggregated structures for photocurrent generation. In the incident photon-to-current efficiency (IPCE) analysis, SD1 dye-sensitized devices exhibited photocurrent generation from both monomeric and aggregated dyes on the TiO2 surface. In contrast, SD2 showed photocurrent generation solely from aggregated states. Despite the introduction of long alkyl chains to reduce dye aggregation and charge recombination, the results indicated preferential charge injection from only the aggregated SD2 dye on TiO2. Fluorescence-quenching experiments indicated an efficient charge transfer from the aggregated SD2 dye to TiO2 compared to that of the monomeric dye. Cosensitization, a method to enhance the light-harvesting efficiency and photocurrent generation in DSSCs, was explored by simultaneously cosensitizing pyridyl-based dyes (SD1 and SD2) with a blue-colored carboxylic acid-based squaraine dye SD4. IPCE analysis demonstrated that both SD1 and SD4 contributed to generating a photocurrent of 9.11 mA/cm(2). The sequential cosensitization of SD1 and SD4 with the coadsorbent CDCA showed the highest performance, with a V-OC of 0.663 V, a J(SC) of 11.43 mA/cm(2), and an efficiency (eta) of 5.20%.
Keywords: co-sensitization; Design; Emmision; Fluorescent Dyes; High-Efficiency; Organic Dye; Ring

Reactive distillation configuration for the production of ethyl acrylate - Gore, Jayram I.; Mahajani, Sanjay M.; Mali, Nilesh A. (CHEMICAL ENGINEERING AND PROCESSING-PROCESS INTENSIFICATION, 2024)
Keywords: ACETIC-ACID; CYCLOHEXYL ACETATE; Design; Dimethyl carbonate